(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2023)
The historical manufacturer of electric traction machines for trams and trolleybuses, the innovative commercial company UMEB, has initiated a joint project with the National Institute of Research and Development for Electrical Engineering ICPE-CA, to design and produce a new line of electric machines that achieve the desired power, starting torque, speed range, and operating temperatures. Following the requests received by UMEB from the integrators of vehicles for the transport of people, the need arose to produce an electric motor characterized by a high torque density and a wide range of operating speeds. The development team selected the technical solution of a permanent magnet and liquid-cooled synchronous motor, carried out the design theme, motor sizing, numerical simulation validation of the project, motor component design, execution, assembly of the prototype motor, and its testing. The resulting TN-EB 21 prototype engine is presented during this innovative development process.